PERAN ILMU KEDOTERAN FORENSIK DALAM PEMBUKTIAN TINDAK PIDANA PENGANIAYAAN - Onan Purba; Rumelda Silalahi (JURNAL RETENTUM, 2020)
In proving a criminal case of persecution related to the body and human life, the role of forensic medicine is very important in helping law enforcers uncover a criminal act that has occurred. The fields of law and medicine cannot be separated in order to prove someone's wrongdoing, this is based on the fact that not all knowledge is controlled by judges. In this case a forensic doctor is able and can help unravel a mystery in the absence of evidence that can be a body or a part of a human body. Judges will not be able to know and understand whether a criminal act has occurred and whether the defendant before the trial has actually committed the crime and can be responsible for the incident, so it is necessary to know the extent to which the role of forensic medicine in proving cases in court.